The Impact of Nutrition, Vaccination, and Warning Signs on Dengue Fever Severity in Children at Doris Sylvanus Hospital - Adelgrit Trisia; Ni Nyoman Sri Yuliani (Lambung Mangkurat University, 2025)
Dengue Fever (DF) is an infectious disease caused by the dengue virus, primarily transmitted by the Aedes mosquito. The incidence and mortality rates, especially among children, have remained alarmingly high. This is largely attributed to the ambiguous clinical manifestations of the disease and the challenges in predicting its severity. Factors such as nutritional status and immunization play a pivotal role in influencing the severity of DF. In a study conducted at dr. Doris Sylvianus General Regional Hospital, we analyzed the impact of these factors on pediatric patients diagnosed with DF. Our observational analytical study followed a cross-sectional approach involving 51 patients aged 0 to 17, admitted between January 2022 and December 2023. Data were sourced from patient medical records and evaluated using the chi-square test. The findings revealed no significant correlation between nutritional status or immunization and the severity of DF symptoms. This implies that maintaining good nutritional health and having a complete vaccination history do not guarantee milder symptoms in DF patients. Ultimately, while nutritional monitoring, vaccination, and early detection of warning signs are vital in managing DF, they do not directly correlate with the severity of the disease. Further research is warranted to explore other influential factors.